“RAIN was planting the seeds”: An Interview with Tom Bender, co-editor of RAIN: Journal of Appropriate Technology - Meredith Gaglio (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
From 1974 through 1980, RAIN: Journal of Appropriate Technology was the foremost “print tool” of the Appropriate Technology, or AT, Movement in the United States. During that period, the Rainmakers, led by Steve Johnson, Lee Johnson, Land de Moll, and Tom Bender, constructed a visionary ecotopia on the pages of their journal, supplying readers with the philosophical grounding, real-world advice, and political conviction to pursue AT projects within their own communities. This article is an abridged transcript of an interview conducted by architectural historian, Meredith Gaglio, with one of RAIN’s co-editors, the late Tom Bender, at his home in Manzanita, Oregon, in April, 2016. In the interview, Bender recollects his introduction to Appropriate Technology, through the work of Ernst Friedrich Schumacher and R. Buckminster Fuller, discusses the foundations of RAIN: Journal of Appropriate Technology, and shares his thoughts on how sustainable change is made.